2011
DOI: 10.1007/s00402-011-1436-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of cemented versus uncemented hemiarthroplasty for displaced femoral neck fractures in older patients

Abstract: The purpose of this review was to assess the effectiveness and safety of cemented versus uncemented hemiarthroplasty for displaced femoral neck fractures in older patients. We searched the Cochrane Library, MEDLINE and EMBASE for published randomized clinical trials comparing cemented with uncemented hemiarthroplasty for femoral neck fractures. Eight trials assessing 1,175 hips were eligible for meta-analysis. The pooled results showed that there was no significant difference between cemented and uncemented gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 31 publications
5
60
2
1
Order By: Relevance
“…Different operative techniques are described in the literature. However, some questions concerning benefits of different approaches, complication rates, fixation (cementless vs cemented), implant design (bipolar vs monopolar) and others are not completely resolved [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Different operative techniques are described in the literature. However, some questions concerning benefits of different approaches, complication rates, fixation (cementless vs cemented), implant design (bipolar vs monopolar) and others are not completely resolved [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment options include THA and bipolar hemiarthroplasty [2,12,18,26]. The optimal surgical treatment of displaced femoral neck fractures is still debated.…”
Section: Discussionmentioning
confidence: 99%
“…No unipolar components were used during the study period for the indication of a displaced femoral neck fracture. Developments in implant fixation techniques have led to the use of uncemented stems in hemiarthroplasties, although studies have shown advantages in the survival with cemented femoral components for this elderly cohort [6,18,26,27]. Second, our intention was not to compare cemented bipolar hemiarthroplasties with THAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations